Knowledge, Mechanical Aptitude, and Age on Dual-Expertise Teacher Competence: A Correlational Study - Nanang Eko Saputro; Purnomo Purnomo; Tuwoso Tuwoso (Pascasarjana Universitas Negeri Malang (UM), 2019)
Abstract: The present study aimed to investigate relations of prior knowledge, mechanical aptitude, and age to competence of dual-expertise teachers. The study was conducted following a research design of ex-post facto. The samples were 102 dual-expertise teachers. To answer its problems, the study collected the data by using questionnaires, tests, and documentation. The data gathered were then analyzed employing desctiptive analysis, regression analysis, and partial correlation analysis. The study found that (1) there is a relation between the prior knowledge, mechanical aptitude, and age to the competence of dual-expertise teachers; (2) a relation is revealed between the prior knowledge and the competence of dual-expertise teachers; (3) a relation is identified between the mechanical aptitude and the competence of dual-expertise teachers; and (4) a relation is found between the age and the competence of dual-expertise teachers.Key Words: prior knowledge, mechanical aptitude, age, competence of dual-expertise teachers, “on-in-on-in” training modelAbstrak: Penelitian bertujuan untuk mengetahui hubungan kompetensi awal, bakat mekanik, dan usia dengan kompetensi guru keahlian ganda. Penelitian ini menggunakan rancangan penelitian ex-postfacto. Sampel penelitian adalah 102 guru keahlian ganda. Pengumpulan data menggunakan kuesioner, tes, dan dokumentasi. Analisis data pada penelitian ini menggunakan analisis deskriptif, analisis regresi ganda, dan analisis korelasi parsial. Hasil penelitian ini adalah: (1) ada hubungan kompetensi awal, bakat mekanik, dan usia dengan kompetensi guru keahlian ganda; (2) ada hubungan kompetensi awal dengan kompetensi guru keahlian ganda sebesar; (3) ada hubungan bakat mekanik dengan kompetensi guru keahlian ganda sebesar; dan (4) ada hubungan usia dengan kompetensi guru keahlian ganda sebesar.Kata kunci: kompetensi awal, bakat mekanik, usia, kompetensi guru keahlian ganda, model pelatihan “on–in–on–in”